2021
DOI: 10.1111/papt.12375
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in experiential avoidance explain changes in anxiety, depression and well‐being after a mindfulness and self‐compassion (MSC) training

Abstract: Objective: The mindfulness and self-compassion (MSC) protocol has shown efficacy in reducing mental illness symptoms and increasing well-being. However, little is known on how the positive outcomes are produced. This study explores how reductions in experiential avoidance following MSC training may explain changes in the participants' levels of anxiety, depression, and well-being. Methods: The 8-week protocol-based MSC training was delivered to 50 participants, and pre-to post-intervention changes in anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“… 46 The connections between self-compassion and such processes (ie lower experiential avoidance, higher tolerance to uncertainty) could contribute to explain self-compassion beneficial effects. For instance, Yela et al 8 found that the reductions in experiential avoidance after a Mindful Self-Compassion (MSC) program delivered to a community sample accounted for changes in depression, anxiety and well-being in a study conducted. However, this suggestion is yet to be tested in a mental health professionals’ sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 The connections between self-compassion and such processes (ie lower experiential avoidance, higher tolerance to uncertainty) could contribute to explain self-compassion beneficial effects. For instance, Yela et al 8 found that the reductions in experiential avoidance after a Mindful Self-Compassion (MSC) program delivered to a community sample accounted for changes in depression, anxiety and well-being in a study conducted. However, this suggestion is yet to be tested in a mental health professionals’ sample.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Specific interventions aimed to cultivate self-compassion skills, such as the Mindful Self-Compassion (MSC) program 4,5 have even been designed. In addition, this particular training protocol, or adaptations of it, have been demonstrated as effective in several studies carried out in community samples [6][7][8] and clinical settings. 9 However, the use of interventions and trainings aimed at cultivating mental health professionals' self-compassion is not a widespread practice yet.…”
Section: Introductionmentioning
confidence: 98%
“…A cross-sectional study demonstrated that low self-compassion may increase avoidance of emotional experiences, which is a particularly problematic emotion regulation strategy (Bakker et al, 2019). Moreover, longitudinal research based on 8-week mindfulness and self-compassion training found that increases in self-compassion were associated with decreases in experiential avoidance between pre- and post-intervention (Yela et al, 2021). Self-compassion training aims to cultivate acceptance, which refers to the ability to allow experiences in the present moment, whether pleasurable, neutral, or painful, to be just as they are (Germer, 2005).…”
Section: Mediating Role Of Self-compassionmentioning
confidence: 99%
“…With an increased understanding, the most determining components can be enhanced and consequently the effectiveness of these programs can be strengthened and optimized ( van der Velden et al, 2015 ; Alsubaie et al, 2017 ). Several mechanisms in the context of MBCT have been proposed and three overlapping yet distinct factors have received considerable consensus: mindfulness skills, self-compassion, and (reduced) experiential avoidance ( Gu et al, 2015 ; Collado-Navarro et al, 2021 ; Medlicott et al, 2021 ; Yela et al, 2022 ). Mindfulness has been defined as awareness that arises through purposefully paying attention to the present moment and doing so without judgment ( Cebolla et al, 2012 ; Parmentier et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, past research examining potential mechanisms of mindfulness-based programs are largely limited to methodologically flawed designs ( Gu et al, 2015 ). For example, there are few studies that have evaluated proposed mechanisms longitudinally (e.g., before, during, and after delivering the intervention) ( Yela et al, 2022 ). Additionally, there are few studies that have investigated clinical MDD populations with TRD and, as a result, there is only preliminary and insufficient evidence evaluating mechanisms at this time.…”
Section: Introductionmentioning
confidence: 99%